2017
DOI: 10.21071/az.v66i255.2523
|View full text |Cite
|
Sign up to set email alerts
|

Parâmetros genéticos para características de crescimento e reprodutivas em bovinos Nelore no Brasil

Abstract: resUMoConhecer o progresso genético e fenotípico de uma população é importante para se avaliar o resultado dos programas de seleção adotados e como elementos norteadores de ações futuras. Assim, objetivou-se estimar parâmetros genéticos, tendências genéticas e fenotípicas dos pesos aos 205 (P205), 365 (P365) e 550 (P550) dias de idade, idade ao primeiro parto (IPP), circunferência escrotal (CE) e intervalos de partos (IDP) de 175.231 bovinos Nelore, nascidos no período de 1967 a 2011 na região Nordeste do Bras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
3
0
4
Order By: Relevance
“…Values of posterior heritability means obtained in this study are consistent with values observed by other authors. Heritability estimates in cattle for weaning weight ranged from 0.11 to 0.25 (Moreira et al, 2015;Santos et al, 2019;Barbosa et al, 2017), from 0.16 to 0.44 for the yearling weight (Moreira et al, 2015;Souza et al 2018;Santos et al, 2019;Barbosa et al, 2017), from 0.17 to 0.44 for post-yearling weight (Moreira et al, 2015;Souza et al, 2018;Santos et al, 2019;Barbosa et al, 2017), and from 0.20 to 0.26 for post-weaning weight gain (Duitama et al, 2015;Santana et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Values of posterior heritability means obtained in this study are consistent with values observed by other authors. Heritability estimates in cattle for weaning weight ranged from 0.11 to 0.25 (Moreira et al, 2015;Santos et al, 2019;Barbosa et al, 2017), from 0.16 to 0.44 for the yearling weight (Moreira et al, 2015;Souza et al 2018;Santos et al, 2019;Barbosa et al, 2017), from 0.17 to 0.44 for post-yearling weight (Moreira et al, 2015;Souza et al, 2018;Santos et al, 2019;Barbosa et al, 2017), and from 0.20 to 0.26 for post-weaning weight gain (Duitama et al, 2015;Santana et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Because of this importance, genetic improvement programs related to growth traits in beef cattle have been developed throughout the country (Santana et al, 2017), aiming at increasing productive and reproductive potential. Estimates of genetic parameters for growth traits in beef cattle are indicators of the response to genetic improvement (Barbosa et al, 2017), allowing classification and selection of the best individuals to be parents in the next generations. One aspect to consider in this context is that several authors have reported on the estimates of genetic parameters in populations of Nelore in different regions of Brazil (Passafaro et al, 2016;Barbosa et al, 2017;Souza et al, 2018;Pereira, 2021) and showed the existence of genetic variability, which allows for genetic progress through selection.…”
Section: Introductionmentioning
confidence: 99%
“…Ademais, outra justificativa para utilização desta característica é especialmente por serem de fácil mensuração (Silva et al 2012) e por apresentar herdabilidades moderadas permitindo possíveis ganhos genéticos ao longo das gerações. As estimativas dos parâmetros genéticos para as características de crescimento em bovinos de corte são indicadoras da resposta ao melhoramento genético a ser alcançado (Barbosa et al 2017), permitindo classificar e selecionar os melhores indivíduos para serem pais nas próximas gerações.…”
Section: Introductionunclassified